2023
DOI: 10.3390/biom13020252
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Hepatic UGT1A1 Increases Plasma Bilirubin, Lowers Plasma Urobilin, Reorganizes Kinase Signaling Pathways and Lipid Species and Improves Fatty Liver Disease

Abstract: Several population studies have observed lower serum bilirubin levels in patients with non-alcoholic fatty liver disease (NAFLD). Yet, treatments to target this metabolic phenotype have not been explored. Therefore, we designed an N-Acetylgalactosamine (GalNAc) labeled RNAi to target the enzyme that clears bilirubin from the blood, the UGT1A1 glucuronyl enzyme (GNUR). In this study, male C57BL/6J mice were fed a high-fat diet (HFD, 60%) for 30 weeks to induce NAFLD and were treated subcutaneously with GNUR or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Compared to UCB, CB may be more readily separated from albumin to protect patients from metabolism disorders [ 17 ]. Regarding the mechanism of action of bilirubin on glycolipid metabolism, it has been found that bilirubin can reduce glucose and lipid accumulation by increasing insulin sensitivity and intracellular glucose uptake, and activating the aryl hydrocarbon receptor (AhR) signaling pathway [ 60 , 61 ]. A meta-analysis found that the overall prevalence of MetS in patients with schizophrenia was 32.5%, and the prevalence in unmedicated patients was also as high as 20.2% [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to UCB, CB may be more readily separated from albumin to protect patients from metabolism disorders [ 17 ]. Regarding the mechanism of action of bilirubin on glycolipid metabolism, it has been found that bilirubin can reduce glucose and lipid accumulation by increasing insulin sensitivity and intracellular glucose uptake, and activating the aryl hydrocarbon receptor (AhR) signaling pathway [ 60 , 61 ]. A meta-analysis found that the overall prevalence of MetS in patients with schizophrenia was 32.5%, and the prevalence in unmedicated patients was also as high as 20.2% [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substrates contained in each array are listed in Supplemental Table 1 . Mouse livers were pooled and measured in triplicate across three chips simultaneously for STK, as previously described in [ [22] , [23] , [24] ]. This approach effectively deals with large batch effects across samples.…”
Section: Methodsmentioning
confidence: 99%
“…are included in Supplemental Table 2 (males) and 3 (females). MEOW (measurements extensively of winners) plots, as described in [ 24 ], were used to interrogate individual kinase activities on substrates considering the confidence of the experimental versus the control groups using the equation: [Log2 Fold Change (FC) of kinase substrates ∗ Δconfidence (experimental hits/mean hits of 2000 random sampling iterations)]. Data input files for STK runs available on the GitHub repository at the following ( https://github.com/The-Hinds-Lab/Liver-Specific-Cpt1a-KO-Kinome-Analysis ).…”
Section: Methodsmentioning
confidence: 99%
“…Current research indicates that UGT1A1 mutation is a benign condition with no significant pathological response, and will not lead to hepatocyte death or chronic liver disease[ 4 ]. Moderate levels of bilirubin are effective physiological antioxidants[ 5 ], and may reduce oxidative stress, alleviate inflammation, prevent fibrosis, and ultimately affect the development of non-alcoholic fatty liver disease[ 6 , 7 ]. Furthermore, elevated levels of bilirubin can inhibit lipid oxidation and delay the development of atherosclerosis, thereby helping to prevent and counteract cardiovascular diseases such as coronary heart disease[ 8 ].…”
Section: Introductionmentioning
confidence: 99%